Biodegradable waterborne polyurethane with modified hydroxyethylcellulose - I. H. Lee; S. Y. Bae; B. K. Kim (eXPRESS Polymer Letters, 2018)
The waterborne polyurethane (WPU)/hydroxyethyl cellulose (HEC) chemical hybrids were synthesized by incorporating vinyltrimethoxysilane (VTMS) modified HEC (VC) into the WPU. Effects of VC on the contact angle, gel content, thermal and mechanical properties of the cast films, and biodegradation in cellulase solution were evaluated. It was found that the VTMS modified HEC provided the WPU with multifunctional crosslinks as well as conventional reinforcing fillers and biodegradability.